Exposure to Phlebotomus argentipes (Diptera, Psychodidae, Phlebotominae) sand flies in rural areas of Bihar, India: the role of housing conditions. - Paritosh Malaviya; Epco Hasker; Albert Picado; Mukesh Mishra; Jean-Pierre Van Geertruyden; Murari Lal Das; Marleen Boelaert; Shyam Sundar (PLoS ONE, 2014)
BACKGROUND:Visceral Leishmaniasis (VL) is a vector-borne infectious disease, caused by the protozoan Leishmania donovani, which is transmitted by phlebotomine sand flies. In an earlier study in Bihar, India, we found an association between incidence of VL and housing conditions. In the current study we investigated the influence of housing structure and conditions in and around the house on the indoor abundance of Phlebotomus argentipes, the vector of VL in this area. METHODS:In each of 50 study villages in Muzaffarpur district, we randomly selected 10 houses. Light traps were installed in each house for one night during three annual peaks of sand fly density over two successive years. Sand flies captured were morphologically identified and segregated by species, sex and feeding status. Data on housing conditions and socio-economic status were also collected. We fitted a linear mixed-effects regression model with log-transformed P. argentipes counts as outcome variable and village as random effect. RESULTS:P. argentipes was found in all but four of the 500 households. There was considerable variability between the years and the seasons. On bivariate analysis, housing structure, dampness of the floor, keeping animals inside, presence of animal dung around the house, and socio-economic status were all significantly associated with sand fly density. Highest sand fly densities were observed in thatched houses. In the multivariate model only the housing structure and socio-economic status remained significant. CONCLUSIONS:Better housing conditions are associated with lower sand fly densities, independent of other socio-economic conditions. However, in this area in Bihar even in the better-built houses sand flies are present.